2007
DOI: 10.1152/jn.01176.2006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Excitability of the Cortical Projections to the Human Tibialis Anterior After Paired Associative Stimulation

Abstract: . Paired associative stimulation (PAS) based on Hebb's law of association can induce plastic changes in the intact human. The optimal interstimulus interval (ISI) between the peripheral nerve and transcranial magnetic stimulus is not known for muscles of the lower leg. The aims of this study were to investigate the effect of PAS for a variety of ISIs and to explore the efficacy of PAS when applied during dynamic activation of the target muscle. PAS was applied at 0.2 Hz for 30 min with the tibialis anterior (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 39 publications
(61 reference statements)
7
127
0
Order By: Relevance
“…Only with this specific interval of 25 ms between the two stimuli was a significant change in the excitability of the cortical projections to the APB observed. A similar protocol has been applied to the TA, although the delay between the two stimuli was reported to be longer (50 ms) for any significant induction of plasticity (Mrachacz-Kersting et al 2007). In the present study, the ES was timed to occur 50 ms before the PN of the MRCP, since the PN is associated to movement execution and may be seen as a more natural activation of the motor cortex compared with TMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only with this specific interval of 25 ms between the two stimuli was a significant change in the excitability of the cortical projections to the APB observed. A similar protocol has been applied to the TA, although the delay between the two stimuli was reported to be longer (50 ms) for any significant induction of plasticity (Mrachacz-Kersting et al 2007). In the present study, the ES was timed to occur 50 ms before the PN of the MRCP, since the PN is associated to movement execution and may be seen as a more natural activation of the motor cortex compared with TMS.…”
Section: Discussionmentioning
confidence: 99%
“…The timing was calculated according to the following equation: mean PN Ϫ 50 ms. The 50 ms represents the mean latency for the afferent inflow resulting from the peripheral stimulus to reach the somatosensory cortex plus a cortical processing delay and is based on previous work (Mrachacz-Kersting et al 2007). Figure 1E, left, shows an example from one patient, where the arrow denotes the instant of the ES being triggered with a delay of 50 ms in relation to the PN.…”
Section: Methodsmentioning
confidence: 99%
“…A strong influence of stimulus timing on recovery extent is not surprising given the ability of cortical and spinal conditioning paradigms to induce substantial changes in functional connectivity in animals and humans, even after SCI (12,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Indeed, when either cortical action potentials (12) or salient increases in EMG activity (21) are used to trigger microstimulation at cortical sites in freely behaving nonhuman primates, substantial and durable changes in motor output can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…PAS induced short-term neuronal adaptations in form of short-term neuronal plasticity. A reversible increase in the excitability of cortical structures is achieved when a sub-threshold stimulus arrives at the post-synaptic cell before a second supra-threshold stimulus (Mrachacz-Kersting et al, 2007) (Hebb’s law of coincident summation 1949). TMS can be used, in combination with PNS, to experimentally induce short-term synaptic plasticity by PAS, also called Hebbian plasticity (Cirillo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The ISI was determined based on a previous study where an ISI of 55 ms was found to be optimal for inducing the greatest increase in the TA MEP amplitude for PAS during rest (Mrachacz-Kersting et al, 2007). A total of 90 stimuli were applied at a rate of 0.05 Hz lasting about 30 min.…”
Section: Methodsmentioning
confidence: 99%